RESULTS OF NEW RUSSIAN INTRAOCULAR LENSES IMPLANTATION - D. D. Dementyev; M. V. Sysoeva; A. V. Shipunova; I. M. Ivanchikova (Oftalʹmologiâ, 2017)
Purpose: to analyze the data obtained from a multicenter study of the hydrophobic IOL Citrin and a hydrophilic IOL Aquamarine implantation and a comparison of the Acrysoft IQ with Citrine and IOL by the given parameters.Patients and methods. A total of 100 IOLs produced by NanOptic (96 hydrophobic IOLs Citrine and 4 hydrophilic IOLs Aquamarine) and 24 IOL Acrysoft IQ were implanted. 7 ophthalmological clinics in different Russian cities took part in the study. The observation period was from 1 to 10 months. The indication for phacoemulsification was age cataract in 99 cases (99 eyes). The clear lens was removed for refractive purpose in one patient (2 eyes) with high degree of myopia. The age of the patients was 34–81. The basic examination was made for patients before the operation. The mean uncorrected visual acuity before the operation was (UCVA) 0.13±0.14 (0.001–0.6), the average corrected visual acuity (BVVA) was 0.32±0.28 (0.001–0.85). All patients underwent standard phacoemulsification.Results. There were no complication in the early postoperative period. In the postoperative period, the mean UCVA was 0.52±0.24 (0.2–1.0), the mean VCVA was 0.75±0.24 (0.3–1.0). In all cases, the refraction obtained was consistent with the prediction. The error in calculating the IOL was minimal and permissible. In 72% cases, the threshold contrast sensitivity was normal or slightly decreased. In some cases, there were difficulties in implantation of a hydrophobic IOL. At the same time, difficulties in implanting the hydrophilic IOL weren’t registered.Conclusions. The first results of implantation of new Russian IOLs on the given parameters appeared to be satisfactory. Further research, including the dynamic long term observation of the implantation results is required.